Multiregion whole-genome sequencing depicts intratumour heterogeneity and punctuated evolution in ovarian clear cell carcinoma. Issue 9 (20th December 2019) - Yin, Xia; Bi, Rui; Ma, Pengfei; Zhang, Shengzhe; Zhang, Yang; Sun, Yunheng; Zhang, Yi; Jing, Ying; Yu, Minhua; Wang, Wenjing; Tan, Li; Di, Wen; et al.
Abstract : Background: Ovarian clear cell carcinoma (OCCC) arises from endometriosis and represents a difficult-to-treat gynaecological malignancy, in part, because its spatial intratumour heterogeneity and temporal evolutionary trajectories have not been explicitly defined. Methods: We performed whole-genome sequencing on six pathologically confirmed patients with OCCC. An R package named KataegisPortal was developed to identify and annotate loci of localised hypermutations. Immunohistochemical staining was conducted on a tissue microarray containing 143 OCCC specimens. Results: Multiregion analysis demonstrated considerable degrees of subclonal diversification, ascribable to dynamic mutagenic processes, as well as macroevolutionary events including the acquisition of aneuploidy and chromoplexy. KataegisPortal unveiled APOBEC-mediated kataegis in the early phases of OCCC pathogenesis. We further showed evidence that APOBEC3A and APOBEC3B were frequently expressed in OCCC and possibly regulated by the MAPK pathway. Notably, APOBEC3B-expressing OCCC displayed favourable prognosis and appreciable immunogenicity manifested by marked cytotoxic T-cell infiltration. Conclusions: These results point to an appealing model of punctuated tumour evolution underlying OCCC neoplastic transformation and progression, which may pose formidable challenges of early detection and intervention, and indicate the intratumour heterogeneity of cancer-driving alterations, yielding important implications for molecular diagnosis and targeted treatment of this lethal disease.